2021
DOI: 10.1016/j.fochx.2021.100148
|View full text |Cite
|
Sign up to set email alerts
|

The structure and flavor of low sodium seasoning salts in combination with different sesame seed meal protein hydrolysate derived Maillard reaction products

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…As a result, the pH value of the system dropped significantly. The result was consistent with a previous study [20].…”
Section: Ph and Browning Degreesupporting
confidence: 94%
“…As a result, the pH value of the system dropped significantly. The result was consistent with a previous study [20].…”
Section: Ph and Browning Degreesupporting
confidence: 94%
“…The color analysis of the SP was conducted following the method described by Hu et al. (2021). The color values were measured using a CR‐400 colorimeter (Konica Minolta).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the Se-reduction capability of these strains was evaluated by analyzing color characteristics quantified in terms of values (Table 2), where values run from negative (green) to positive (red). [30,31] The red/green values (a*) were found to increase with increasing Na 2 SeO 3 concentration, indicating a shift towards a deeper red color resulting from the reduction of Na 2 SeO 3 to SeNPs. [32] Studies have shown that when levels of Na 2 SeO 3 in the environment reach a certain threshold, toxic Na 2 SeO 3 is reduced to produce non-toxic SeNPs, which forms part of their detoxification mechanism.…”
Section: Analysis Of Se-tolerance and Se-reduction Enhancementmentioning
confidence: 96%